KAJIAN KUAT LENTUR BALOK BETON BERTULANGAN BAMBU WULUNG TAKIKAN TIPE V DENGAN JARAK 2 CM DAN 3 CM - Kultsum, Ummi; Setiya Budi, Agus; Sunarmasto, Sunarmasto (Program Studi Teknik Sipil FT UNS, 2014)
In construction industry, the reinforcement of concrete beam and steel is a construction material which is commonly used in building structures,where the compressive strength of concrete and the tensile strength of steel is a complementary combination. However, the use of steel as reinforcementstill get some problems such as the higher price and its a product of the mining of non-renewable and will run out someday. To overcome theseproblems, bamboo is selected as an alternative of steel reinforcement which is renewable natural product, easily obtained, inexpensive, and have ahigh tensile strength. This research aims to determine the tensile strength of bamboo wulung used to calculation and analysis of the bending capacityof the bamboo to the steel reinforcement, by making the beam specimen as many as 12 pieces with a size of 11 cm x 15 cm x 170 cm. Three of thefirst six beam specimen planted bamboo wulung reinforcement with V-type notch by notch distance of 2 cm and 3 cm, and then The next threebeam specimens planted ø 8 mm reinforcement steel and three unreinforced beam specimens for comparison. Quality concrete is planned f'c = 17.5MPa. The experiments performed in Laboratorium Struktur/Structures Laboratory, FT UNS on the concrete age of 28 days by giving twopoints of concentrated loads at a distance of 1/3 span beam from the pedestal. Based on the analysis and test results can be concluded, the nominalmoment of the test results in beam specimen planted reinforcement bamboo wulung notches type V with distance of 2 cm, 3 cm, steel ø 8 mm andbeam unreinforced are consecutive obtained a mean of 0.436 tonm, 0.441 tonm, 0.516 tonm and 0.111 tonm. Nominal moment analysis basedin beam specimen planted reinforcement bamboo wulung notches type V on yield strength internodia, nodia and steel ø 8 mm are consecutiveobtained a mean of 0.454 tonm, 0.378 tonm and 0.505 tonm. The ratio of flexural capacity on beam specimen planted reinforcement bamboowulung notches type V with distance of 2 cm and 3 cm obtained of 0.962 and 0.971 on the yield strength internodia. While the yield strength onnodia, ratio of flexural capacity beam reinforcement bamboo wulung notches type V with distance of 2 cm and 3 cm obtained of 1.156 and 1.167.In beam reinforcement steel ø 8 mm ratio of flexural capacity obtained 1.022. Average value of the maximum deflection at maximum loadhappens at 1/3 middle span or on the recording dial gauge 2 whose position is at the middle of the beam span. The pattern of cracks that occur asexpected, which of the 12 pieces beam specimen, the average collapse occurred on 1/3 middle span beams and section in concentrated load point.